Hasil Audit, Jabatan Gubernur, Kinerja Keuangan Daerah Dan Dampaknya Terhadap Kesejahteraan Masyarakat - Sarjono Sarjono (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2016)
The purpose of this study was to analyze the factors that influence social welfare. The factors are audit opinion, financial performance, follow-up of audit recommendations, and the tenure of governors in the 34 provinces. The data used in this study is secondary data and in the form of panel data, and have been analyzed by multiple regression. The results showed that the financial performance and follow-up of audit recommendation have the positive and significanteffect on social welfare. But, the audit opinion and the tenure of governor have negative and not-significant effect on social welfare.